3D Printing as an Aid in Acetabular Defects Compared to Established Diagnostics – a Survey - Babasiz, Mari; Roos, Jonas; Kasapovic, Adnan; Kaczmarczyk, Robert; Welle, Kristian (Zeitschrift für Orthopädie und Unfallchirurgie, 2025)
The treatment of acetabular defects in revision arthroplasty is an increasing challenge. Different classifications have been introduced for preoperative planning to achieve the best possible result. 3D printing is a way to better visualize and understand these defects. The aim of this study was to facilitate classification, provide young doctors with a better understanding of complex defects, and ultimately improve preoperative planning and patient safety.The study was conducted at the 2022 BOUT congress, where health care professionals were provided with X-rays, a computed tomography (CT) scan, and a 3D print to classify acetabulums according to Paprosky and ADC. A questionnaire was administered to gather information on their familiarity with the classification systems and perception of 3D models in the clinic.The study involved 14 participants, mostly resident physicians, with some familiarity with the Paprosky and ADC classifications. The 3D printing method resulted in the highest rate of correct classifications for acetabular defects compared to X-ray and CT imaging. Participants found the 3D model useful for clinical applications and rated it higher than X-ray and CT imaging for classifying acetabular defects.Acetabular defects present a challenge in assessment, preoperative planning, and surgical management due to their complex anatomy. Overall, we were able to show that the use of a 3D model increases the accuracy in the classification of acetabular defects. The use of 3D printing in orthopedics and trauma surgery is showing more and more advantages and has opened up new methods for the education of medical students and young surgeons.
Keywords: acetabular defects; revision arthroplasty; 3D printing; orthopedic surgery; medical imaging